Improving transient gene expression and agroinfiltration‐based transformation effectiveness in Indonesian orchid Phalaenopsis amabilis (L.) Blume - Dionysia Heviarie Primasiwi; Yekti Asih Purwestri; Endang Semiarti (Universitas Gadjah Mada, 2024)
Transient gene expression is an approach used to study transient genes across various species, with infiltration by Agrobacterium tumefaciens (agroinfiltration) being a commonly used method. Agroinfiltration offers a simple and effective means of delivering transgenes into the plant genome. An alternative method for enhancing the quality and productivity of orchids as ornamental plants is genetic modification through agroinfiltration. Although Agrobacterium‐mediated genetic transformation by immersion has been used on the Phalaenopsis amabilis (L.) Blume species of orchid, transformation efficiency using the immersion technique remains relatively low and the method itself is challenging due to its requirement for aseptic handling. The application of agroinfiltration in P. amabilis has not previously been reported. This study investigates the impact of the injection site, acetosyringone concentration, bacterial density (OD600), and injection volume to determine the optimum conditions for agroinfiltration on P. amabilis. The results demonstrated that injection site had a noticeably distinct impact on transformation effectiveness, with the abaxial position of the leaf being the optimal site for Agrobacterium culture suspension injection. While adjustments in acetosyringone concentration, bacterial density (OD600), and injection volume did not significantly affect transformation efficiency, they did influence the peak time of GFP fluorescence. Acetosyringone at a concentration of 200 µM, an OD600 of 1.0 for Agrobacterium culture, and an injection volume of 500 µL effectively accelerated GFP expression duration.